2004
DOI: 10.1038/sj.thj.6200411
|View full text |Cite
|
Sign up to set email alerts
|

Long-term management of chronic DIC associated with inoperable aortic aneurysm with low molecular weight heparin

Abstract: Chronic DIC is a rare complication of aortic aneurysm. Surgical correction is the treatment of choice but for inoperable patients or those with continued DIC after surgery heparin can be used to control the coagulopathy. A case with inoperable multiple aortic aneurysm and chronic DIC managed successfully with dalteparin over a long period is discussed in this report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
(4 reference statements)
0
9
0
1
Order By: Relevance
“…A diagnosis of DIC associated with aortic dissection was made on the basis of the observations characterized by haemorrhagic diathesis, prolonged plasma coagulation time, hypofibrinogenemia and thrombocytopenia. Chronic DIC is a rare complication of acute or chronic aortic dissection [6] and can be a difficult longterm problem [8]. There might be several reasons for chronic DIC associated with aortic dissection for a long time after endovascular stent-grafting in this case.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A diagnosis of DIC associated with aortic dissection was made on the basis of the observations characterized by haemorrhagic diathesis, prolonged plasma coagulation time, hypofibrinogenemia and thrombocytopenia. Chronic DIC is a rare complication of acute or chronic aortic dissection [6] and can be a difficult longterm problem [8]. There might be several reasons for chronic DIC associated with aortic dissection for a long time after endovascular stent-grafting in this case.…”
Section: Discussionmentioning
confidence: 98%
“…Although there are some previous studies that LMWH treatment in chronic DIC associated with aneurysm was effective [7,8,17], we had to avoid LMWH treatment for two reasons: severe thrombocytopenia and obvious haemorrhagic diathesis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have demonstrated that the effective adjunctive treatments for chronic DIC due to aortic aneurysm were: continuous heparin infusion (11), subcutaneous injection of low molecular weight heparin (6,(12)(13)(14), the intravenous injection of danaparoid with the oral administration of tranexamic acid (15), and thrombomodulin (16,17) with or without platelet and FFP transfusion for the acute phase of exacerbation of chronic DIC. However, the intravenous or subcutaneous administration of these medicines for the prevention of an exacerbation of chronic DIC in outpatients for an extended period of time is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…テンダー PXA260300 を追加したところ,エンドリークは 消失した (Fig. 3) 11) 2003 61/M DA TEVAR Yoon 12) 2004 55/M DA Medication Majumder 13) 2004 89/W TAA+AAA 50×50/38×38 Medication Ontachi 14) 2005 63/M AAA 50×50 Medication Miyahara 15) 2007 60/M DA Medication Chalasani 16) 2007 73/M AAA 66×69 Medication Nishimura 17) 2007 84/M AAA 50×45 Medication→Ope Murai 18) 2008 69/M AAA Femoral A 52×50 R90×75 L43×40 Medication→Ope Yuan 19) 2009 70M TAA+AAA 87×87/72×72 Medication→Ope Togami 20) 2009 67/M DA Medication 2009 89/M AAA Medication Fuchigami 21) 2009 78/M FA Ope Domoto 22) 2011…”
unclassified